𝑞-Analogue of Wright Function - Moustafa El-Shahed; Ahmed Salem (Abstract and Applied Analysis)
We introduce a 𝑞-analogues of Wright function and its auxiliary functions as Barnes integral representations and series expansion. The relations between 𝑞-analogues of Wright function and some other functions are investigated.